Negosiasi Masyarakat Perkotaan dalam Memenuhi Kebutuhan Pendidikan Agama Islam bagi Anak - Moh Fatkur Rohman (PT. Nawa Edukasi Nusantara, 2025)
The dynamics of the development of urban communities in urban areas are one of the trends in cultural development that are very massive. This is also the starting point for the development of the paradigm of urban society in determining Islamic religious education for their children. The best education, strategic facilities, and good teaching quality, are important factors in considering Islamic religious education for children. This creates negotiations between parents on the reality of the need for Islamic education for their children. This research uses a qualitative type of research, based on field research. The analysis of this study uses the Miles and Hubermann model. From this study, it can be concluded that urban communities in urban areas have various options for consideration in determining the best Islamic religious education for children. The influencing factors are prestige, social motives, and the quality of spiritual education that can be provided by educational institutions. The emergence of other motives outside the educational aspect are factors that also contribute to parents in determining their children's choice of Islamic education.